EXTRACTION AND CHARACTERIZATION OF FICUS GLOMERATA FOR ANTIOXIDANT ACTIVITY - PRAKASH, ANIL; SARANGDEVOT, YUVRAJ SINGH; VYAS, BHUPENDRA; ROY, SONALI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: This study is focused on the evaluation of phytochemical constituents and antioxidant properties contained in Ficus glomerata. Various phytochemical constituents such as alkaloid, glycoside, total phenolic content, flavonoid, and carbohydrate constituent content were evaluated. Methods: Extraction of plant F. glomerata was obtained using methanol as solvent using soxhlation. Antioxidant properties in F. glomerata extract were evaluated using free radical scavenging activity using 2, 2-diphenyl-1-picrylhydrazyl method. Antioxidant activity of the extract of F. glomerata was expressed as gallic acid equivalent. Results: The result obtained from the study was in support of the use of F. glomerata as a natural antioxidant against free radicals that are formed in the pathogenesis of many metabolic disorders. Conclusion: The results obtained from the research found to conclude that antioxidant properties derived from natural extracts may be a promising alternative to synthetic oxidants and may aid in avoiding the side effects associated with the use of synthetic antioxidants. Other than the antioxidant properties, a correlation was observed between the total phenolic content and the antioxidant properties.